Hypertension delays viral clearance and exacerbates airway hyperinflammation in patients with COVID-19 - Trump, Saskia; Lukassen, Soeren; Anker, Markus S.; Chua, Robert Lorenz; Liebig, Johannes; Thürmann, Loreen; Corman, Victor Max; Binder, Marco; Loske, Jennifer; Klasa, Christina; Krieger, Teresa; Hennig, Bianca P.; et al. (Nature biotechnology, 2021)
In coronavirus disease 2019 (COVID-19), hypertension and cardiovascular diseases are major risk factors for critical disease progression. However, the underlying causes and the effects of the main anti-hypertensive therapies - angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) - remain unclear. Combining clinical data (n = 144) and single-cell sequencing data of airway samples (n = 48) with in vitro experiments, we observed a distinct inflammatory predisposition of immune cells in patients with hypertension that correlated with critical COVID-19 progression. ACEI treatment was associated with dampened COVID-19-related hyperinflammation and with increased cell intrinsic antiviral responses, whereas ARB treatment related to enhanced epithelial-immune cell interactions. Macrophages and neutrophils of patients with hypertension, in particular under ARB treatment, exhibited higher expression of the pro-inflammatory cytokines CCL3 and CCL4 and the chemokine receptor CCR1. Although the limited size of our cohort does not allow us to establish clinical efficacy, our data suggest that the clinical benefits of ACEI treatment in patients with COVID-19 who have hypertension warrant further investigation.